The concept of economic - environmental crimes in the Czech Republic - Vasylchuk, L. B. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The article refers to economic environmental crimes, that is, those illegal encroachments on the environment that are perceived as the most serious. On the example of the Czech Republic, a post-communist state in Eastern Europe that joined the European Union, the main problems related to criminal prosecution are presented. As a result of the analysis, the key factors of insufficient prosecution for economic environmental crimes were identified, namely, in particular, high latency, low removal of registered suspicions, lenient punishment and ineffectiveness of criminal repression against corporations. The unfortunate state of blaming this type of anti-terrorist acts is the basis of the reasons that lie in the basis of criminal law, criminology and the evil policy of the state. It has been established that the causes of malice in the Czech Republic in the sphere of foreign affairs are in the vicinity of it and the countries of the European Union, however, it is obvious that the high latency of the Czech Republic is equal to the countries of the EU. The head rank of this is the position of the sovereign administration, in order to be seen in the absence of evil. The negative role of the negative role of the lower social responsibility of the communities, as well as the presence of their activity, which is directly related to the initiatives of the investigation of anti-right actions, which is to block the serious environment. We are important to accept both contractual approaches, as from the point of view of law-making, as from the point of view of the law, as from the point of view of the stosuvannia, as it would be positively influenced by the meaning of the factor. It has been established that the punishment for economic environmental crimes in the Czech Republic is not satisfactory. Improvements should be implemented at all levels: from amending legislation to strengthening responsibility for committing illegal acts. Penalties for the most serious environmental crimes should be comparable to the most serious economic crimes (property and tax crimes), i.e. with the possibility of imprisonment for a term of at least 2-10 years, which will pose a real threat of imprisonment.